The Evolution of Religious Discourse in Contemporary Islam: A Linguistic-Philosophical Perspective - Kirom, Makhiulil; Sutaman, Sutaman (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This research examines the relationship between words and it’s meaning in religious terms and their impact on the formation of social identity, based on Ludwig Wittgenstein's language games theory. The research employs a qualitative approach, utilizing literature review and social discourse analysis of religious terms within the social context of Indonesian society. Terms such as hijrah, jihad, sharia, kafir, and bid'ah are analyzed to understand how their meanings shift and evolve over time. The findings reveal that the meanings of these terms are dynamic and heavily influenced by social contexts and usage within the community, playing a significant role in shaping and reinforcing the social identity of specific groups. Thus, this study emphasizes the importance of understanding religious terms within a broader socio-cultural framework, where language functions not only as a means of communication but also as a dynamic instrument for shaping social identity. By demonstrating how the shifting meanings of religious terms influence group boundaries and social interactions, this research contributes to a deeper understanding of religious discourse and its role in the negotiation of identity within Indonesian societyKeywords: word, meaning, religious discourse, language game, contemporary Islam